ナンキョク ロケット ニヨル オーロラ タイ コウカ デンシ ノ カンソク a. ニュウシャ リュウシ ト オーロラ ダイ 1カイ キョクイキ ニオケル デンリケン ジキケン ソウゴウ カンソク シンポジウム PART 1 - 奥谷, 晶子; オクタニ, ショウコ; 和田, 雅美; ワダ, マサミ; 竹内, 一; タケウチ, ハジメ; 小玉, 正弘; コダマ, マサヒロ; 今井, 喬; イマイ, タカシ; OKUTANI, Shoko; WADA, Masami; et al. (国立極地研究所, 1979)
P(論文) 1976年1月からの1年間に,オーロラ電子検出器搭載の観測ロケット5台が,昭和基地から打ち上げられた.うち1台は静穏日に,残り4台はオーロラ活動時に行われた.電子検出器は,比例計数管とプラスチックシンチレーション計数管である.測定の下限エネルギーは40 keVである.ここでは,オーロラ出現時における高速電子の高度分布,ピッチ角分布について速報する.そしてすでに報告した静穏時における特性と比較する. During one year from January 1976, five sounding rockets carrying the electron detector were launched from Syowa Station, Antarctica. One of them was made on a geomagnetically quiet time, while the others all encountered a certain degree of auroral disturbance. The rocket-borne detector consists of both proportional and plastic scintillation counters and can measure high energy electrons greater than 40 keV. Preliminary results thereby obtained are presented, giving an account of characteristics of vertical profile and pitch angle distribution of energetic electrons during auroral disturbances, compared with those for the quiet time. departmental bulletin paper